Kantisele Ritual: A Strategy for Treating Tisele Disease in the Muna Tribe of Southeast Sulawesi - Nurwiati; Asrul, Taufiq Al-Islam; Sama, Abinus (Arden Jaya Publisher, 2025)
This paper aims to determine the desires and classification of Kantisele rituals in the Muna Ethnic community in Tongkuno Selatan District, Muna Regency. This type of research is qualitative descriptive research. The determination of informants was determined by purposive sampling, which is a technique for determining informants intentionally. With a total of 9 informants, this study was obtained through participant observation, in-depth interviews, literature studies, and documentation studies. The results of the study indicate that the traditional kantisele treatment process has seven stages, the first stage is search mantra, the third is rubbing water on the crown of the head, the fourth is rubbing water on the right and left ears, the fifth is rubbing water on the right and left arms, the sixth is rubbing water with the thumbs of the hands side by side on the right and left, and the seventh is rubbing water with the thumbs of the right and left sides. The continuity of the Kantisele ritual in the Muna Ethnic Community in South Tongkuno District, Muna Regency from the time of their ancestors until now is still carried out by the Muna community, especially in Lianosa Village, South Tongkuno District. In fact, most people already know the Kantisele ritual because their parents always pass it on to their children, considering that this Kantisele speech means a lot to them in the future. The classification of the Kantisele ritual in the Muna Community, South Tongkuno District, Muna Regency, namely: Kantisele Katelebuta, Kantisele Koghendu, Kantisele, Kahalano Lalo, Kantisele Kakalano Lalo, and Kantisele Kasantuno Lalo.ing for veins/dumada, the second is reading water by reciting the kantisele/bhatata.